Das Kulturerbe deutschsprachiger Juden Eine Spurensuche in den Ursprungs-, Transit- und Emigrationsländern - Kotowski, Elke-Vera (Europäisch-jüdische Studien - Beiträge, 2017)
As part of the German Jewish Cultural Heritage project, the contributors to this volume examine the cultural influence of the German-speaking Jewish intelligentsia around the world. This influence continues to be felt in many countries of origin and exile without being adequately reflected in collective consciousness. This volume makes a substantive contribution to the search for traces of German-speaking Jewish culture in the wake of emigration.